The Effect of Transparency and Accountability on Local Government Performance With Government Agency Performance Accountability Evaluation as an Intervening Variable - Desmalita, Winda; Setyadi, Bakti (DINASTI RESEARCH, 2025)
This study seeks to investigate the impact of transparency on the performance of local government within the context of accountability in the government agencies of Muara Enim Regency. It further explores the correlation between accountability and the quality of performance demonstrated by these local government agencies. Moreover, the research assesses the function of performance accountability evaluation as an intervening variable in the interplay between transparency, accountability, and performance. The primary data for this study was gathered through questionnaires distributed to State Civil Apparatus involved in the implementation of AKIP and the preparation of OPD performance accountability reports. The research focuses on 35 Regional Apparatus Organizations (OPD) in Muara Enim Regency, with a sample size of 300 respondents selected through purposive sampling methods. Path analysis using LISREL software was the data analysis technique applied. The findings reveal that both transparency and accountability have a significant effect on local government performance, as well as on the evaluation of government agency performance accountability. Furthermore, the evaluation of performance accountability within government agencies significantly influences local government performance, both directly and indirectly through the channels of transparency and accountability.